De social à socialista: publicação e recepção do romance Os Mistérios de Paris, de Eugène Sue, na imprensa fluminense (1844-1857) - Sant'Ana, Mateus Ribeiro de (2022)
This paper analyzes the publication and reception of the French novel The Mysteries of Paris (1842-1844), by Eugène Sue, in the newspaper Jornal do Commercio, where it was initially published in 1844-45, and in other Rio de Janeiro newspapers in the 1840s and 1850s. The novel, which had already presented relevant success in its native country, brought a series of social criticisms typical of the great European urban centers, besides making a strong dialogue with the socialist authors of the period. Throughout the dissertation, we will see to what extent Sue's novel actually approaches or distances itself from the idea of socialism in a broad sense, appropriated by different political movements that were often in conflict. This analysis is done to understand how a novel that dealt with problems of European capitals had impacted the agrarian and slave society of the Empire of Brazil. Trough the reading and analysis of the novel and publications in the Rio de Janeiro press, we will see that Sue's text is situated precisely in a moment in which the very perception of the term 'socialism' undergoes a severe alteration, which directly impacts on the very association of the author and his work with the term and consequently on its reading.